15 : Broadening the scope for just socioecological transformations : Ideas, structures, and alliances - Ramcilovic-Suominen, Sabaheta; Gram-Hanssen, Irmelin (Routledge, 2025)
This concluding chapter weaves together the threads and concepts introduced in the book to propose the premise that ideas and ontologies, on one hand, and the structures or physical reality they represent, on the other, are inextricably linked part-wholes of the same “entity”. The chapter emphasizes that while the book presents different approaches to and examples of socioecological transformations, their focus on justice - either as an underlying motivation for change (to address the condition of injustice) and/or as a guiding principle for the process of change (i.e. as a means to an end)“is the shared theme that cuts across all the contributions. The chapter continues with several calls and invitations: (i) a call for a broader ontological inquiry in socioecological transformations, (ii) a call for engaging a broader range of root causes and responses to socioecological violence, and (iii) a call for solidarity-based alliance building between the varied often polarized sides and strategies of action. It uses the term intraconnectedness as the motivation for coming together in solidarity to address different manifestations of the same underlying cause of colonial-racial-capitalist “ontologies structures”.
Keywords: socioecological transformations